STABLE AND SUSTAINABLE KNOWLEDGE SOCIETIES: A Gandhian Perspective - Jose, Jeff Shawn (Journal of Dharma, 2019)
This paper examines Gandhian philosophy and practice to reinterpret UNESCO's educational vision towards establishing stable and sustainable knowledge societies. The uniqueness of the Gandhian perspective is its ability to withstand the dominant political, philosophical and religious challenges with its contextually rooted, spiritually oriented, socially responsible and human person centred reinterpretations. UNESCO’s educational vision - Learning: The Treasure Within published in 1996 is a catalyst in establishing stable and sustainable knowledge societies. Consistent changes and challenges in knowledge societies necessitates the reinterpretation of this educational vision. The four pillars of learning in this educational vision are analysed together with four aspects of Gandhian philosophy and practice: ‘learning to know’ and Nai Talim, ‘learning to do’ and ashrams, ‘learning to live together’ and constructive programme and ‘learning to be’ and swaraj. The paper discusses this confluence of the UNESCO’s theoretical approach of four pillars of education with Gandhian pragmatic philosophy and practice to offer a contextually rooted and future-oriented outlook for reinterpreting the educational vision for establishing stable and sustainable knowledge societies.